Shehu Variational Iteration Method For Solve Some Fractional Differential Equations - Boulekhras, Amina; Belghaba, Kacem (Communications in Mathematics and Applications, 2022)
The idea proposed in the work is to extend the Shehu transform method to resolve the nonlinear fractional partial differential equations by combining them with the variational iteration method (VIM). We apply this technique to solve nonlinear fractional equations as nonlinear time fractional Fokker Planck equation.
Keywords: Caputo fractional derivate; Variational iteration method; Shehu transform; Fokker-Planck equation; Telegraph equation of space